PENGGUNAAN KARTU PERSILANGAN GENETIKA TRIHIBRIDA SEBAGAI MEDIA PEMBELAJARAN BIOLOGI DAPAT MENINGKATKAN HASIL BELAJAR DAN AKTIVITAS SISWA KELAS XII MADRASAH ALIYAH NEGERI BINJAI - Fauziah Fauziah (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2021)
The purpose of this study was to increase student activity in Biology lessons. Based on research and data processing, it was found that the use of the Trihybrid Genetic Crosses card (three different traits) as a Biology learning medium, can improve the learning outcomes of class XII students of Madrasah Aliyah Negeri Binjai in the 2019/2020 school year in Biology lessons on Trihybrid Genetic Crosses (three different traits). ), this can be seen from the calculation of the correlation value in the first cycle between the pre-test to the first daily test of 0.827 with a t-test value of 8.333, and the second cycle between the post-test to the second daily test of 0.943 with a t-test value of 16.075. The use of the Trihybrid Genetic Cross card (three different traits) as a Biology learning medium, can increase the activity of class XII students of Madrasah Aliyah Negeri Binjai in the 2019/2020 school year in Biology lessons on Trihybrid Genetic Crosses (three different traits), this can be seen from the presence students during classroom action research (CAR), from 90% of the first cycle increased to 95% and 100% of the second cycle. Key words : Trihybrid Genetic Cross Card as Biology Learning Media, Learning Outcomes, Activities